2013
DOI: 10.1111/bij.12191
|View full text |Cite
|
Sign up to set email alerts
|

Divergence and molecular variation in common whelkBuccinum undatum(Gastropoda: Buccinidae) in Iceland: a trans-Atlantic comparison

Abstract: The dispersal and history of species affects their genetic population structure at both small and large geographical scales. The common whelk, Buccinum undatum, is a widespread subtidal gastropod in the North Atlantic that has no planktonic larvae and has thus limited dispersal capacity. The snail, which has been harvested by humans for centuries, is highly variable in morphology. To evaluate the population structure in the rich fishing grounds in western Iceland and its divergence from samples across the Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 62 publications
6
28
0
Order By: Relevance
“…SSR markers have been widely used as highly effective DNA markers in the study of molluscan population genetics (Arthofer et al, 2011;Pálsson et al, 2014). In this study, 65 novel microsatellite loci were isolated and some of them were used to analyze the population genetics of Bellamya spp in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSR markers have been widely used as highly effective DNA markers in the study of molluscan population genetics (Arthofer et al, 2011;Pálsson et al, 2014). In this study, 65 novel microsatellite loci were isolated and some of them were used to analyze the population genetics of Bellamya spp in China.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite markers are a useful marker system for the analysis of the population genetics of many snail species (Arthofer et al, 2011;Pálsson et al, 2014;Rivero-Wendt et al, 2014). Gu et al (2012a,b) first developed SSR DNA markers for B. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…Although introductions from multiple sources can alleviate these bottlenecks, these mixed populations still exhibit a pattern of subsampling, with alleles identical to or closely descended from those found in more phylogenetically diverse indigenous populations (Geller et al ., ; Frankham, ; Hauber et al ., ; Lacoursière‐Roussel et al ., ; Cahill & Viard, ). By contrast, natural post‐glacial trans‐Atlantic dispersal is expected to result in a distribution including the intermediate landmasses of Iceland and Greenland and one or more monophyletic lineages on each side of the Atlantic (Krebes, Blank & Bastrop, ; Panova et al ., ; Palsson et al ., ) If C. volutator was recently introduced to the NWA from the NEA, we expect genetic diversity in the NWA to be a subsample from more phylogenetically diverse populations in the NEA. Consistent with this prediction, we found that all genetic diversity in the NWA was identical to or recently descended from that found in the NEA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The closed season has also resulted in some displaced effort, whereby French owners have expressed interest in buying Jersey-registered vessels to operate in Jersey exclusive waters during the French closed season, further increasing fishing effort upon Jersey whelk stocks. The recent study by Pálsson et al (2014) highlights the short larval dispersal and thus genetic difference of whelks populations on a relatively small scale and in turn, their sensitivity to overexploitation via displaced or concentrated fishing effort. We would thus suggest a joint closed season in both Jersey and France, at the same time of year.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in other regions around the UK and Europe have shown that once an area has been 'fished-out' it can take a relatively long time for the population to recover, if at all, as there is little inward migration of other whelks (Hancock, 1963;Himmelman and Hamel, 1993;Valentinsson et al, 1999). A recent study by Pálsson et al (2014) suggests that genetically different populations of common whelks can occur within small coastal areas, yet are independent of geographical or shortest distances on sea.…”
Section: Introductionmentioning
confidence: 99%